United Republic of Tanzania Public Expenditure and Financial Accountability Review 2008 - World Bank (Washington, DC, 2014)
Rising inflation represents a serious challenge for the government, including fiscal policy. By December 2008, inflation has risen to 13.5 percent, far above the government target of five percent since 2004. It is important the government continue its effort to reduce inflation through monetary and fiscal policies, including reducing inflationary pressures on the budget by controlling wage bill growth in line with medium-term pay policy. The 2008-09 Medium-Term Expenditure Framework (MTEF) projected optimistic targets for domestic revenue and, at a same time, pessimistic targets for foreign aid. Although domestic revenue has been rising over the recent past, the targeted 18.5 percent of Gross Domestic Product (GDP) in revenue effort is high given the fact that revenue has increased by only one percent of GDP annually in the past five years. It is important to improve reliability of the macro-framework by sustaining efforts to develop capacity in macro-fiscal policy and macro-modeling, which is an important tool for the government to properly assess expected levels of domestic revenue collection over the medium term. Although some major achievements have been obtained in capacity building program, priority areas for intervention have also been identified for 2009. These areas are: (i) strengthening of macroeconomic model (MACMOD) and the macro policy framework paper, taking into account the world economic crisis as well as new data developments in Tanzania; (ii) initiating MTEF upgrades (both central and sector) as well as program budgeting starting with the ministry of health and social welfare; and (iii) preparing the second edition of the budget background and medium term framework for 2009/10 - 2011/12.